Lean Management Analysis in the Emergency Department of RSAL Dr. R. Oetojo Sorong to Reduce Mortality among Appendicitis Surgery Patients - Indra Widjayanto; Cicilia Windiyaningsih; Ahdun Trigono (Universitas Pahlawan Tuanku Tambusai, 2026)
This study analyzes the implementation of lean management in the emergency room of Dr. R. Oetojo Sorong Naval Hospital to identify obstacles (waste) and its effectiveness in reducing the mortality rate of appendicitis patients. The method used was qualitative descriptive, involving 31 informants through in-depth interviews, observation, and documentation. The results of the study identified four main types of waste before the intervention: waiting, inventory, transportation/motion, and defects. The implementation of lean strategies, such as the establishment of a Satellite Pharmacy Depot, the use of Handy Talkies, and the application of the Alvarado Score as a substitute for ultrasound, proved to be effective in significantly reducing waiting times. The average waiting time from arrival to the decision to operate (door-to-incision) was successfully reduced from 3–6 hours to less than 60 minutes, even reaching 30 minutes in critical cases. The study concluded that lean management contributes significantly to patient safety by keeping treatment within the golden period, thereby preventing fatal complications such as sepsis. Although optimization in the emergency department has been achieved, systemic improvements in downstream units such as operating rooms are essential to ensure the sustainability of overall service efficiency.